Effects of argatroban, danaparoid, and fondaparinux on trombin generation in heparin-induced thrombocytopenia - Tardy-Poncet, Brigitte; Combe, Marion; Piot, Michèle; Chapelle, Céline; Akrour, Majid; Tardy, Bernard (Thrombosis and Haemostasis, 2013)
There is no in vitro data on the comparison of the effects of danaparoid, argatroban and fondaparinux on thrombin generation in patients with heparin-induced thrombocytopenia. It was the study objective to compare the in vitro anticoagulant potential of argatroban, danaparoid and fondaparinux using a thrombin generation assay TGA on a mixture of control platelet-rich plasma (PRP) and HIT patient platelet-poor plasma (PPP). The plasma of seven patients with a clear HIT diagnosed at our institution was selected. Mixtures of donor PRP and patient PPP were incubated with unfractionated heparin 0.2 U.mL-1, argatroban at 600 ng.mL-1, argatroban at 400 ng.mL-1, danaparoid at 0.65 IU.mL-1 and fondaparinux at 1 [uni03BC]g.mL-1. Thrombin generation was assessed by calibrated thrombinography. The percentage of inhibition of the endogenous thrombin potential observed with argatroban at 600 ng.mL-1 was statistically significantly higher compared with those observed with fondaparinux (median: 53.6% vs. 3.9%; p = 0.031) but not compared with argatroban at 400 ng.mL-1 and danaparoid. The percentage of inhibition of the thrombin peak observed with argatroban at 600 ng.mL-1 was statistically significantly higher compared with those observed with danaparoid (median: 71.2 vs. 56.8; p = 0.031) and fondaparinux (mean: 71.2 vs. 30; p = 0.031) but not with argatroban at 400 ng.mL-1. In conclusion, the in vitro effect of argatroban and danaparoid on thrombin generation seems to corroborate the results of clinical studies of these drugs in the treatment of HIT in term of efficiency. Fondaparinux showed a very small effect on thrombin generation evaluated by calibrated thrombinography.
Keywords: Heparin-induced thrombocytopenia; thrombin generation; direct thrombin inhibitor; danaparoid; fondaparinux